RESOCIALIZATION OF CONVICTS IN PLACES OF IMPRISONMENT OF THE STATE CRIMINAL ENFORCEMENT SERVICE OF UKRAINE - Bogatyrev, Ivan; Kolodchyna, Alla (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: scientific and methodological understanding of the resocialization of convicts in places of imprisonment of the State Criminal Enforcement Service of Ukraine. Research methods: the article uses the dialectical method of cognition, general scientific and special research methods. In particular, the structural-functional, sociological and dogmatic method. Results: the questions covered in the article allowed us to consider the resocialization of convicts in places of imprisonment, as one of the priority directions of the state policy in the field of punishment and probation of the Ministry of Justice of Ukraine. It is noted that the process of resocialization of convicts in places of imprisonment goes through all stages of serving the sentence. Discussion: the scientific article analyzes the effectiveness of using the resocialization tool on convicts while serving their sentence. The author’s concept of resocialization is formulated. It has been proven that the resocialization of convicts in places of imprisonment of the State Criminal Enforcement Service of Ukraine is one of the priority directions of the functioning of the bodies and institutions for the execution of punishments, as well as the leading task of the penitentiary systems of most countries of the world, and therefore its research corresponds to the request of the criminal and executive science of Ukraine. Summarizing the theoretical achievements of the science of penal law and the results of the study, we came to the following conclusions: Resocialization of convicts in places of deprivation of liberty by the State Penitentiary Service of Ukraine is one of the stages of serving a criminal sentence by a convict, which is based on the legal, pedagogical, and psychological changes of the convicted person, which should have a positive impact on his conscious behavior in isolation and prepare the convict for the return of an appropriate, independent, generally accepted, and socio-normative life in society. It has been established that not all convicts in places of deprivation of liberty of the State Penitentiary Service of Ukraine have a positive attitude towards resocialization, and this is due to the fact that their behavior is characterized by a low level of offenses while serving their sentences and a low readiness to perceive measures of a social and educational nature. Education does not play a significant role in the formation of the socially useful orientation of convicts, and the activities of public organizations are of a formal nature. The priority area of work of the staff of places of deprivation of liberty of the State Penitentiary Service of Ukraine should be an individual approach to the planning and implementation of measures aimed at achieving the goal of punishment, which will be ensured only through the use of means of resocialization for convicts. It is proposed to enshrine in Article 6 of the Criminal Code of Ukraine the criteria that would make it possible to establish the degree of achievement of the goal of resocialization of a person serving a sentence in places of deprivation of liberty of the State Penitentiary Service of Ukraine.